Private Information Acquisition via Freedom of Information Act Requests Made to the Securities and Exchange Commission - Glaeser, Stephen; Schonberger, Bryce; Wasley, Charles E.; Xiao, Jason J. (The Accounting Review, 2023)
ABSTRACT There is limited evidence about when, why, and which individuals incur costs to acquire nonpublic information about a firm, largely due to the difficulty of observing private information acquisition. To overcome this difficulty, we obtain data on Freedom of Information Act (FOIA) requests submitted to the Securities and Exchange Commission (SEC). We predict and find that perceived information asymmetry between managers and outsiders resulting from both proprietary and agency costs triggers FOIA search. We categorize organizations making FOIA requests using their business descriptions and find that many, including law and intellectual property firms, are not expressly interested in obtaining information for near-term equity trading. Instead, their search activity relates to determinants beyond financial characteristics, including patent litigation and executive turnover. Taken together, we provide evidence on private information search by a relatively unexamined set of organizations and shed new light on the function of the SEC’s Office of FOIA Services. JEL Classifications: D82; D83; M41.